The history of economics a course for students and teachers - Backhouse, Roger 1951-; Tribe, Keith 1949- (Agenda publishing, 2023)
As a broad introduction to the history of economic thought - based on courses the authors have taught for many years - this book provides an overview for students and teachers who have not had the opportunity to cover the development of the field of economics in its historical context. The text is presented as a series of twenty-four lectures, which can be used as the basis for self-study or for the delivery of a course. Each lecture presents an outline of aims, a select bibliography, a chronology, an overview of between 3,000 and 4,000 words, and questions for further study or reflection